The water footprint of pig farms in Ireland based on commercial farm data - Shilpi Misra; Corina E. van Middelaar; Keelin O’Driscoll; Amy J. Quinn; Imke J.M. de Boer; John Upton (Cleaner Water)
Livestock production is getting increased attention due to its impact on natural resources, and freshwater is one such limited resource. To reduce the pressure on freshwater use and develop sustainable livestock systems from farm-to-fork we need to study the whole production cycle, and look for hotspots of major freshwater use. Considering this, we chose intensive pork production as our focal livestock system, since it is one the most eaten meats globally. We focused on pork production in Ireland and studied the freshwater use (green and blue) from cradle-to-farm gate using the water footprint (WFP) method. Detailed farm data (e.g. diet composition, production data) were combined with on-farm water meter data to explore variations in water consumption between farms, and potential explanatory variables for differences in consumption between farms. So far, there have been no WFP studies in pork production that explored this, and insight into variation could help to identify options for improvement. We analyzed the direct (on-farm) and indirect (off-farm) green and blue water footprint of 10 Irish pig farms. Our results show that the average total WFP, including the direct and indirect water footprint, was 2537 L/kg pork, which is at the low end of previously published studies. The indirect green water footprint related to the production of purchased feed was responsible for the largest share (99 %) of the total WFP. The direct blue water footprint formed only a minor component of the total WFP (14 L/kg pork), with drinking water playing the major role. We can conclude from this study that variation in WFP between the least and most efficient farms was small (Q3-Q1 = 181 L/kg pork); nevertheless, this indicates that efficiencies of around 7 % could be gained by the least efficient cohort of farms by adjusting on-farm management practices. We also found a weak negative correlation between WFP and farm size, and WFP and meat produced. Overall, this study suggests that to reduce the burden on freshwater resources and reduce the pork WFP, future research should focus on the feed related impacts.